Exploration of the risk factors contained within the UK's existing domestic abuse risk assessment tool (DASH): do these risk factors have individual predictive validity regarding recidivism?. Issue 1 (9th January 2017) - Almond, Louise; McManus, Michelle; Brian, David; Merrington, Daniel Peter
Abstract : Purpose: The purpose of this paper is to explore risk factors contained in the existing UK domestic abuse (DA) risk assessment tool: domestic abuse, stalking and harassment and honour-based violence (DASH) for individual predictive validity of DA recidivism using data from Devon and Cornwall Constabulary. Design/methodology/approach: In total, 1, 441 DA perpetrators were monitored over a 12-month period, and 270 (18.7 per cent) went on to commit a further DA offence. The individual risk factors which were associated and predictive of increased risk of recidivism were identified. Findings: Only four of the individual risk factors were significantly associated with an increased risk of DA recidivism: "criminal history", "problems with alcohol", "separation" and "frightened". Therefore, 21 of the risk factor items analysed could not discriminate between non-recidivist and recidivist perpetrators. Only two risk factors were able to significantly predict the recidivist group when compared to the non-recidivist group. These were identified as "criminal history" and "separated". Of those who did commit a further DA offence in the following 12 months, 133 were violent and 137 were non-violent. The risk factors associated with these types of recidivism are identified. Practical implications: The implications for UK police practice and the DASH risk assessment tool are discussed. By identifying key individual factors that can prioritise those individuals likely to recidivate and the severity of that recidivism, this could assist police decision making regarding the response and further prevention of DA incidents. The validation of association between individual factors and DA recidivism should improve the accuracy of risk levels. Originality/value: This is the first large-scale validation of the individual risk factors contained within the UK's DA risk assessment tool. It should be noted that the validity of the DASH tool itself was not examined within the current study.